Multiple Taxation And Business Survival in Anambra State, Nigeria - Nkiru, Ezeanokwasa Francisca; Chinelo, Nwagbala Stella; Raphael, Nwachukwu; Ejike, Ani Anthony (Development Policy and Management Review (DPMR), 2024)
The study investigated the relationship between multiple taxation and business survival in Awka, Anambra state. The specific objective was to evaluate the effectiveness of existing tax policies in fostering a conducive environment for business survival and to analyze the coping strategies businesses employ in response to multiple taxations. A survey research design was employed on a population of 330 from 11 small-scale entrepreneurs in Awka Anambra State. Taro Yamane’s formula was used to obtain a sample size of 319. This study employed primary data gathered through structured questionnaires distributed to managers/owners of 319 Small and Medium-sized Enterprises (SMEs) in Awka, Anambra State. The hypotheses were tested using the Chi-squared test with the aid of Statistical Package for Social Sciences V.22. The findings revealed that there is a significant relationship between the effectiveness of existing tax policies and multiple taxations (p-value = 0.000); there is a significant relationship between multiple taxations and coping strategies employed by businesses (p-value = 0.000). The study therefore recommends that the Anambra State Government should streamline and harmonize tax collection processes across different agencies to minimize duplication and reduce the financial burden on businesses, thereby fostering a more conducive environment for business growth and investment.